2011
DOI: 10.1021/bi201436n
|View full text |Cite
|
Sign up to set email alerts
|

Oxy Intermediates of Homoprotocatechuate 2,3-Dioxygenase: Facile Electron Transfer between Substrates

Abstract: Substrates homoprotocatechuate (HPCA) and O2 bind to the FeII of Homoprotocatechuate 2,3-dioxygenase (FeHPCD) in adjacent coordination sites. Transfer of an electron(s) from HPCA to O2 via the iron is proposed to activate the substrates for reaction with each other to initiate aromatic ring cleavage. Here, rapid-freeze-quench methods are used to trap and spectroscopically characterize intermediates in the reactions of the HPCA complexes of FeHPCD and the variant His200Asn (FeHPCD-HPCA and H200N-HPCA) with O2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(119 citation statements)
references
References 42 publications
6
110
0
2
Order By: Relevance
“…44,46 Since initial submission of this work, the equivalent intermediate for the native substrate HPCA (H200N-HPCA Int1 ) has also been trapped and spectroscopically characterised. 21 The M€ ossbauer parameters (d ¼ 0.48 and DE Q ¼ 0.95) are similar to those measured for the slow substrate. This intermediate is found to contain high-spin Fe III antiferromagnetically coupled to a radical, which is most likely substrate based, 21 and is assigned as a Fe III -(hydro)peroxo bound to a semiquinone level ligand, entirely consistent with the electronic structure predicted here for the hydroperoxo species.…”
Section: Hydroperoxidesupporting
confidence: 65%
See 1 more Smart Citation
“…44,46 Since initial submission of this work, the equivalent intermediate for the native substrate HPCA (H200N-HPCA Int1 ) has also been trapped and spectroscopically characterised. 21 The M€ ossbauer parameters (d ¼ 0.48 and DE Q ¼ 0.95) are similar to those measured for the slow substrate. This intermediate is found to contain high-spin Fe III antiferromagnetically coupled to a radical, which is most likely substrate based, 21 and is assigned as a Fe III -(hydro)peroxo bound to a semiquinone level ligand, entirely consistent with the electronic structure predicted here for the hydroperoxo species.…”
Section: Hydroperoxidesupporting
confidence: 65%
“…This observation has led to the suggestion that since the reactivity is not dependent on the redox potential of the metal, oxygen activation and substrate oxidation occurs without a change in metal oxidation state. 11,12,21 Instead of a redox change, it is proposed that the metal simply assists in the transfer of the electrons from the substrate to O 2 . This proposal is supported by a density functional theory (DFT) study which suggested that the +2 oxidation state is maintained through the peroxo-bridge formation up until O-O cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Ringcleaving dioxygenases active toward these noncatecholic compounds belong to the cupin superfamily and utilize a mononuclear Fe II center for catalysis. Their catalytic strategy has been proposed to involve a one-electron transfer to dioxygen, possibly via transient formation of an Fe III -O 2 · Ϫ intermediate, as observed in type I extradiol dioxygenases (83,84), which are members of the VOC superfamily (5). However, it should be emphasized that compared to the thoroughly studied extradiol dioxygenase reaction mechanism, much less experimental evidence is available on the catalytic mechanism of the cupin-type ring-cleaving dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent rearrangement and O-O bond cleavage gives a seven-membered lactone intermediate and an Fe II -bound hydroxide ion, which hydrolyzes the lactone to yield the 2-hydroxymuconate semialdehyde product (Fig. 1b) (44,71,72,78,83,84).…”
mentioning
confidence: 99%
“…My student Stephanie Groce showed that mutation of the active site's histidine 200 to any of several other amino acids greatly slowed the turnover of 4-NC and HPCA, so intermediates could potentially be trapped (38). Finally, Michael Mbughuni used a newly developed rapid freeze quench (RFQ) device to trap intermediates from reaction of the variants with 4-NC and other substrates for EPR and Mössbauer studies (39,40). Similar studies revealed the role of tyrosine 257 in distorting the aromatic ring of the substrate to promote electron transfer to the O 2 (41,42).…”
Section: Slowly Finding Transient Intermediates In Dioxygenasesmentioning
confidence: 99%